Pengaruh proporsi biji nangka (Artocarpus heterophyllus L.) dan kacang hijau (Phaseolus radiatus L.) pada pembuatan sosis nabati - Kunti Mufarikha; Muh Aniar Hari Swasono; Deny Utomo (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Jackfruit seeds and green beans can be used as a substitute for animal protein in making sausages. The purpose of this study was to obtain the right proportion of jackfruit seeds to the correct addition of mung bean flour for the manufacture of vegetable sausage products in terms of physicochemistry and organoleptic. The method used in this study was a 2 factor completely randomized design consisting of 9 treatments and three replications. The treatments were given in the form of the proportion of jackfruit seed flour (N1: 25%, N2: 50%, N3: 75%) with green beans (K1: 25%, K2: 50%, K3: 75%). The parameters measured were protein content test(Method Kjeldahl), texture (Method Texture Profile Analysis), and sensory test (Hedonic Method, Soekarto 1985). The sensory test used is a hedonic scale with 25 untrained panelists. Test of protein content and texture used data from the previous research literature. The results of this study indicated that the higher the proportion of jackfruit seeds and green beans had a significant effect on the parameters of protein content, texture, and organoleptic properties. From literary data, the best parameter of protein content is N3K1 (75% jackfruit seed flour + 75% green bean flour). While the best organoleptic value is the proportion of N1K3 (25% jackfruit seed flour + 25% green bean flour).